Influencing COBRAs: the effects of brand equity on the consumer's propensity to engage with brand-related content on social media. (2nd January 2021) - Schivinski, Bruno; Muntinga, Daan G.; Pontes, Halley M.; Lukasik, Przemyslaw
ABSTRACT: This research examines whether perceptions of brand equity influence consumers' propensity to engage with brand-related content on social media. By combining two frameworks: consumer-based brand equity (CBBE) and consumers' online brand-related activities (COBRAs) we develop two conceptual models and empirically test their validity. Using survey data from respondents across a range of brands, we estimate conceptual models from both a macro- and a micro-relationship perspective. From the macro-relationship perspective, findings suggest that consumer-based brand equity positively drives consumers' behavioral engagement with brands on social media. From the micro-relationship perspective, findings indicate that brand associations influence the consumption and contribution of brand-related social media content, while brand loyalty additionally influences the creation of brand-related social media content. Finally, brand quality was found to negatively effect consumers' behavioral engagement: the lower the perceived quality, the more individuals consume and contribute brand-related content to social media.